2022
DOI: 10.1055/a-1798-1925
|View full text |Cite
|
Sign up to set email alerts
|

INOVASIA Study: A Multicenter Randomized Clinical Trial of Pravastatin to Prevent Preeclampsia in High-Risk Patients

Abstract: Objective To determine if treatment with pravastatin prevents preeclampsia in pregnant patients at risk for preeclampsia. Material & Methods The study was performed in four major tertiary hospitals in Surabaya, Bandung, and Makassar between 2017-2021. Pregnant women at high risk of developing preeclampsia were recruited and randomized into an intervention group and control group. The control group received low dose aspirin (80 mg) and calcium (1 g) daily, while the intervention group received additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
(229 reference statements)
0
5
0
Order By: Relevance
“…Pravastatin is an oral statin used to lower LDL cholesterol and triglycerides, which also has anti-inflammatory actions. A trial in 173 women at high risk of developing pre-eclampsia reported that daily pravastatin from the second trimester (14-20 weeks of gestation) until delivery significantly reduced the rate of preterm pre-eclampsia (13.8% versus 26.7% in the control group) and preterm birth 271 . Pravastatin may not be effective at preventing term pre-eclampsia: there was no reduction in the incidence of term pre-eclampsia in this 271 or another trial of 1,120 women at high risk of developing term pre-eclampsia given daily pravastatin from 35-37 weeks of gestation to delivery 272 .…”
Section: Preventionmentioning
confidence: 99%
“…Pravastatin is an oral statin used to lower LDL cholesterol and triglycerides, which also has anti-inflammatory actions. A trial in 173 women at high risk of developing pre-eclampsia reported that daily pravastatin from the second trimester (14-20 weeks of gestation) until delivery significantly reduced the rate of preterm pre-eclampsia (13.8% versus 26.7% in the control group) and preterm birth 271 . Pravastatin may not be effective at preventing term pre-eclampsia: there was no reduction in the incidence of term pre-eclampsia in this 271 or another trial of 1,120 women at high risk of developing term pre-eclampsia given daily pravastatin from 35-37 weeks of gestation to delivery 272 .…”
Section: Preventionmentioning
confidence: 99%
“…For example, 2 small randomized placebo‐controlled trials, conducted by the National Institute of Child Health and Human Development Obstetric‐Fetal Pharmacology Research Centers (NICHD‐OPRC) Network, in which pravastatin 10 and 20 mg were used daily starting at 12‐16 weeks, showed that compared to placebo, pravastatin use among those with a history of severe preeclampsia that required delivery at <34 weeks was associated with lower rates of preeclampsia, preeclampsia with severe features, and indicated preterm delivery before 37 weeks 52,53 . Similarly, the Indonesia Pravastatin to Prevent Preeclampsia Study (INOVASIA) showed that pravastatin (20 mg twice daily) added to standard of care was associated with lower rates of preterm preeclampsia (<37 weeks) and preterm birth, as well as better perinatal and neonatal outcomes (including lower rates of low and very low birth weight and higher Apgar scores) 54 . On the other hand, a large multicenter trial randomly assigned 1120 pregnant people at high risk (≥1 in 20 likelihood) for term preeclampsia to receive pravastatin 20 mg daily versus placebo from 35 to 37 weeks of pregnancy until delivery or 41 weeks 55 .…”
Section: Policy Changes and Current State Of Affairsmentioning
confidence: 96%
“…52,53 Similarly, the Indonesia Pravastatin to Prevent Preeclampsia Study (INOVASIA) showed that pravastatin (20 mg twice daily) added to standard of care was associated with lower rates of preterm preeclampsia (<37 weeks) and preterm birth, as well as better perinatal and neonatal outcomes (including lower rates of low and very low birth weight and higher Apgar scores). 54 On the other hand, a large multicenter trial randomly assigned 1120 pregnant people at high risk (≥1 in 20 likelihood) for term preeclampsia to receive pravastatin 20 mg daily versus placebo from 35 to 37 weeks of pregnancy until delivery or 41 weeks. 55 While pravastatin was not effective in preventing preeclampsia in this trial, 55 likely due to its being started too late in pregnancy, the study demonstrates the safety of pravastatin in pregnancy, especially in the late third trimester, a critical time of myelination for the developing fetus.…”
Section: Statins For Preeclampsia Preventionmentioning
confidence: 99%
“…Pravastatin (20 mg bid) can be used to prevent preeclampsia and preterm birth in high-risk women; compared to control, pravastatin reduced preterm birth (16.1 vs. 36%, p=0.003, OR=0.340), and was generally related to better perinatal outcomes [36].…”
Section: Preeclampsiamentioning
confidence: 99%